Economy-Wide Model of the Philippine Economy: Preliminary Version - Caesar B. Cororaton (Philippine Institute for Development Studies (PIDS), 1997)
Utilizing the Jemio and Vos Financial Computable General Equilibrium, this paper presents the simulation results of the economic adjustments during 1987-1993, focusing on the impact of the adjustments on factor payments, income distribution and on macroeconomy such as GDP, prices and sectoral production. The simulation period has been selected since the economy has exhibited wide swings during these years. Prompted by the need to improve efficiency and to stabilize the economy, the government has embarked on a number of structural adjustment and stabilization programs. Analyses in this study are preliminary due to the need for updating the JV model that accounts for various factors. However, preliminary policy insights are offered towards the conclusion.
Keywords: 330; liberalization; computable general equilibrium (CGE)